A compartimentação hidrogeológica do Sistema Aquífero Serra Geral (SASG) e Sistema Aquífero Guarani (SAG): um estudo na região da escarpa basáltica nordeste do Rio Grande do Sul - Silva, Rafaela Christ da (Universidade do Vale do Rio dos Sinos, 2019)
The study area, located in the southern portion of the Paraná Basin, in the northeast of the State of Rio Grande do Sul, Brazil, has as supply sources two important aquifer systems, the Guarani (SAG) and the Serra Geral (SASG). The first, constituted by the secondary porosity in the volcanic rocks of the Serra Geral Formation and the second, by the primary porosity in the sandstones of the Botucatu Formation. As it covers a lithological contact zone, the tectonic structures that intercept the volcanic spill piles can affect the SAG sandstone rocks and, depending on their characteristics such as orientation and type of fracturing, provide the connection between the two aquifers, directly affect its productivity , and promote hydrogeological compartmentation. For the present study, data from 375 wells that capture groundwater from the SASG, the SAG and both systems were used, in order to evaluate the hydrodynamic characteristics, potentiometry and altimetry of the lithological contact. These data were analyzed along with regional structural lineaments, joint measurements in more than 100 outcrops of volcanic and sandstone rocks, and petrographic analyzes to assess porosity and cement types. The results demonstrated the occurrence of distinct hydrogeological compartments controlled by fault zones of NW, NNW, and NNE orientation, connection by joints and, locally, faults. The textural and compositional characteristics of sandstones control the preservation or obliteration of the porous system and determine its productive behavior as an aquifer. The contact surface between the Botucatu and Serra Geral formations is favorable for the circulation and storage of groundwater as corroborated by 93% of the wells that crossed this surface. The integration of results allowed proposing a conceptual hydrogeological model integrating the Guarani and Serra Geral aquifer systems.
Keywords: Fluxo subterrâneo; Conexão fraturado-granular; Lineamentos; Compartimentalização tectônica; Bacia do Paraná; Underground flow; Fractured-granular connection; Lineaments; Tectonic compartmentalization; ACCNPQ::Ciências Exatas e da Terra::Geologia